The Effect of Using Podcast-Based Video on Student Learning Outcomes - Kesuma, Dany Wijaya; Soepriyanto, Yerry; Oktaviani, Herlina Ike (Universitas Negeri Malang, 2024)
Podcasts are media files distributed via the internet that can be accessed repeatedly by its users. This study aims to determine the effect of podcast-based video media on the learning outcomes of learners. The subjects of this study were educational technology students class of 2023. data collection was carried out using tests. This research includes quasi-experimental quantitative research. This research uses the Independent Sample T-Test Test. From the results of data processing, it was found that the Asymp.Sig (2-tailed) value was 0.000